Application of the Activity Based Costing Calculation Method in Determining the Cost of Production PT. Sakura Makmur Wijaya in the city of Surabaya - Darul Asmawan; Achmad Daengs GS; Enny Istanti; Rina Dewi; Diana Zuhro (Journal of Managerial Sciences and Studies, 2023)
The research carried out by this researcher was a qualitative descriptive study by obtaining data through documentation, literature study, observation and interviews. This research aims to compare whether determining the cost of production using the Activity-Based Costing method is more appropriate than using the traditional method at PT. Sakura Makmur Wijaya. Researchers took samples of products produced by the company, namely gondola shelves, bookshelves and warehouse shelves in 2016. Calculating the cost of production using traditional methods which are currently still carried out by the company, the results for gondola shelves were IDR. 10,329,489,695.58, bookshelf Rp. 3,448,701,959.66, and warehouse shelves amounting to Rp. 1,290,430,635.75. Meanwhile, using the Activity Based Costing method, the results obtained for Gondola Shelves were IDR 10,322,044,996.50, for Bookshelves IDR 3,444,432,305.13, and for Warehouse Shelves IDR. 1,302,144,989.37. The results of the research show that calculating the cost of goods manufactured using the Activity Based Costing System when compared with the traditional system calculation gives lower results for Gondola Shelf and Bookcase products, except for Warehouse Shelves. Differences occur due to overhead rates being charged for each product. In the traditional system, the costs for each product are only charged to one cost driver, namely the product units produced. Meanwhile, in the Activity-Based Costing System method, factory overhead costs for each product are charged to many cost drivers, so that the Activity Based Costing System is able to track the costs incurred by product types precisely based on the consumption of each activity required and can be used as an alternative by company in allocating its costs.